In vitro susceptibilities of Brucella melitensis isolates to eleven antibiotics - Loukaides Feidias; Psaroulaki Anna; Christidou Athanasia; Ioannidis Alexandros; Turkmani Aun; Tselentis Yiannis (BMC, 2006)
Abstract Background Brucellosis is an endemic disease present in many countries worldwide, but it is rare in Europe and North America. Nevertheless brucella is included in the bacteria potentially used for bioterrorism. The aim of this study was the investigation of the antibiotic susceptibility profile of brucella isolates from areas of the eastern Mediterranean where it has been endemic. Methods The susceptibilities of 74 Brucella melitensis isolates derived from clinical samples (57) and animal products (17) were tested in vitro. The strains originate from Crete (59), Cyprus (10), and Syria (5). MICs of tetracycline, rifampicin, streptomycin, gentamicin, norfloxacin, ciprofloxacin, levofloxacin, trimethoprim/sulfamethoxazole, ampicillin, amoxicillin/clavulanic acid, and erythromycin were detected by E-test method. The NCCLS criteria for slow growing bacteria were considered to interpret the results. Results All the isolates were susceptible to tetracycline, streptomycin, gentamicin, ciprofloxacin, norfloxacin, and levofloxacin. Two isolates presented reduced susceptibility to rifampicin (MIC value: 1.5 mg/l) and eight to SXT (MIC values: 0.75-1.5 mg/l). Erythromycin had the highest (4 mg/l) MIC90value and both norfloxacin and erythromycin the highest (1.5 mg/l) MIC50 value. Conclusion Brucella isolates remain susceptible in vitro to most antibiotics used for treatment of brucellosis. The establishment of a standardized antibiotic susceptibility method for Brucella spp would be useful for resistance determination in these bacteria and possible evaluation of bioterorism risks.